Endothelial Dysfunction A Novel Paradigm - Abukabda, Alaeddin; Fonner, Christopher (IntechOpen, 2023)
The endothelium is a "fluid" and an ever-evolving biological component of the cardiovascular system. It plays important roles in regulating immunology, inflammation, and angiogenesis, among other functions. This book provides a comprehensive review of the endothelium, with a focus on novel aspects of endothelial dysfunction and its treatment.